Lung cancer incidence in female rises significantly in urban sprawl of Shanghai after introduction of LDCT screening. (June 2019) - Liang, Fei; Wu, Chunxiao; Gu, Haiyan; Zhu, Meiying; Xuan, Zeliang; Jiang, Yonggen; Chen, Haiquan; Fu, Chen; Zheng, Ying
Highlights: Lung cancer incidence increased significantly from 2011 to 2015 in women in urban sprawl of Shanghai. Lung cancer mortality in women in urban sprawl of Shanghai did not decreased in the same time period. The incidence pattern of lung cancer in female in suburban of Shanghai did not change after 2011. Abstract: Objectives: LDCT screening for lung cancer has been widely used in China since the release of the NLST trial data in 2011, but little is known about its impact on the incidence and mortality rates of lung cancer in China. Methods: Official cancer registry data of lung cancer incidence and mortality were collected by Shanghai Municipal Center for Disease Control and Prevention from 2005 to 2014. Two districts (Xuhui and Songjiang Districts) were selected to represent populations with different levels of accessibility to LDCT. Incidence and mortality age-standardized rates (ASRs) were calculated using the Segi/Doll 1960 world standard population. Trends in lung cancer incidence and mortality rate over time, the average annual percent change (APC) and the corresponding 95% confidence interval (CI) were calculated using Joinpoint. Results: In Shanghai, lung cancer incidence rate in men did not change significantly between 2005 and 2014 (APC = 0.76%; 95% CI: -0.27%, 1.80%; P = 0.127); while lung cancer incidence in women increased significantly (APC: 5.50%; 95% CI: 2.94%, 8.13%; P = 0.001). In Xuhui district, where eight tertiary hospitals was located, including Shanghai Cancer Center and Shanghai Chest Hospital, both of which provided LDCT lung cancer screening for eligible patients, the incidence rate of lung cancer increased significantly in women only since 2011(APC: 19.84%, P < 0.001). Overall mortality rate of lung cancer showed a significantly decreasing trend from 2005 to 2014 in men (APC = -2.68%, P = 0.009) but not in women (APC = -0.91%, P = 0.305). In Songjiang district, where limited access to LDCT was provided, lung cancer incidence in women increased significantly between 2005 and 2014 (APC: 5.42%, P = 0.001). Lung cancer incidence rates did not change significantly in men in either district from 2005 to 2014. Mortality rate of lung cancer did not change significantly from 2005 to 2014 in both men (APC = -0.51%, P = 0.259) and women (APC = -1.46%, P = 0.186). Conclusion: There is a steady increase in the incidence of lung cancer in women, especially after the wide use of LDCT screening, but without a clear mortality reduction.